Role of midsole hollow structure in energy storage and return in running shoes - Liu, T.; Matijevich, E. S.; Chu, Z.; Yang, F.; Nigg, B. (Journal of Biomechanics, 2024)
Understanding the relationship between footwear features and their potential influence on running performance can inform the ongoing innovation of running footwear, aimed at pushing the limits of humans. A notable shoe feature is hollow structures, where an empty space is created in the midsole. Presently, the potential biomechanical effect of the hollow structures on running performance remains unknown. We investigated the role of hollow structures through quantifying the magnitude and timing of foot and footwear work. Sixteen male rearfoot runners participated in an overground running study in three shoe conditions: (a) a shoe with a hollow structure in the forefoot midsole (FFHS), (b) the same shoe without any hollow structure (Filled-FFHS) and (c) a shoe with a hollow structure in the midfoot midsole (MFHS). Distal rearfoot power was used to quantify the net power generated by foot and footwear together. The magnitude and timing of distal rearfoot work and ankle joint work were compared across shoe conditions. The results indicated that MFHS can significantly (p = 0.024) delay distal rearfoot energy return (3.4 % of stance) when compared to Filled-FFHS. Additionally, FFHS had the greatest positive (0.425 J/kg) and negative (-0.383 J/kg) distal rearfoot work, and the smallest positive (0.503 J/kg) and negative (-0.477 J/kg) ankle joint work among the three conditions. This showed that the size and location of the midsole hollow structure can affect timing and magnitude of energy storage and return. The forefoot hollow shoe feature can effectively increase distal rearfoot work and reduce ankle joint work during running.